The Clinical Frailty Scale and incidence of adverse outcomes in older patients with hip fractures in Qatar - Syamala, Shirmila; Tarazona-Santabalbina, Francisco José; Passarelli, Jorge Luis; Sathian, Brijesh; Nadukkandiyil, Navas; Al Hamad, Hanadi (Frontiers in Medicine, 2025)
BackgroundStudies conducted on Western populations have shown that the Clinical Frailty Scale (CFS) is a major predictor of adverse outcomes in older patients with hip fractures; however, there are no data on Middle Eastern populations, who may be culturally and ethnically different. We examined the association between the preoperative Clinical Frailty Scale and multiple adverse outcomes in a cohort of patients with hip fractures (aged 60–96 years) in Qatar.MethodsThis prospective, single-center observational cohort study included 155 patients aged ≥ 60 years with hip fractures from Qatar. These patients underwent a Clinical Frailty Scale assessment at baseline and were followed to evaluate four outcomes of interest: incident delirium, postoperative complications, all-cause mortality within a year, and increased length of stay (LoS) (LoS ≥ 14 days).ResultsA total of 155 patients with hip fractures (average age 74.6 years, 46.5% women) were included in the study. At baseline, 72.2% had a Clinical Frailty Scale score of <5, 12.3% had a score of 5, and 15.5% had a score > 5. Higher baseline scores on the Clinical Frailty Scale were strongly and positively associated with delirium, postoperative complications, and all-cause mortality, but there was no association with length of hospital stay. Compared to the patients with Clinical Frailty Scale scores < 5, those with scores > 5 had significantly higher multivariable risk ratios (RR) (with 95% confidence interval [CI]) for various outcomes. Specifically, the RR for delirium was 7.76 (3.17–18.97), for postoperative complications, it was 3.59 (1.20–10.77), for all-cause mortality, it was 6.39 (1.45–28.20), and for length of stay ≥14 days, it was 1.43 (0.75–2.73).ConclusionThe Clinical Frailty Scale was positively associated with delirium, postoperative complications, and all-cause mortality but not with length of hospital stay in patients with hip fractures from Qatar.